2018
DOI: 10.1080/24750573.2018.1517466
|View full text |Cite
|
Sign up to set email alerts
|

Ischemia-modified albumin: a unique marker of global metabolic risk in schizophrenia and mood disorders

Abstract: OBJECTIVE: Conformational change in the last four amino acid of the albumin's N-terminus is called ischemia-modified albumin (IMA). Metabolic stress factors such as ischemia, hypoxia, acidosis or endothelial injury may cause these conformational modifications. In this study, we hypothesized that the plasma IMA level changes might help to determine the global metabolic risk in bipolar disorder (BD), unipolar depression (UD), and schizophrenia (SZ). Therefore, it was aimed to investigate metabolic risk factors a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 45 publications
(68 reference statements)
0
5
0
1
Order By: Relevance
“…IMA's diagnostic value in psychiatric disorders, such as AD, schizophrenia, and bipolar disorders, is controversial [101,102]. An increase in IMA, IMAR, and some markers for oxidative stress, such as advanced oxidation protein products (AOPP), ceruloplasmin, and prooxidant-antioxidant balance (PAB), has been shown in AD, the most common form of dementia in the elderly population [99,119].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…IMA's diagnostic value in psychiatric disorders, such as AD, schizophrenia, and bipolar disorders, is controversial [101,102]. An increase in IMA, IMAR, and some markers for oxidative stress, such as advanced oxidation protein products (AOPP), ceruloplasmin, and prooxidant-antioxidant balance (PAB), has been shown in AD, the most common form of dementia in the elderly population [99,119].…”
Section: Neurological Disordersmentioning
confidence: 99%
“…In a study, no significant difference was found in serum IMA levels in bipolar disorder patients during the remission period when compared with the control group [22]. However, another study showed increased IMA levels in bipolar disorder patients during the remission period as compared to the control group, but no significant difference was found in unipolar depression patients [23]. Data from a limited number of studies evaluating IMA levels in psychiatric disorders differ.…”
Section: Discussionmentioning
confidence: 92%
“…CRP is an APR that rapidly reacts to inflammatory processes as well as the major protein carrier for serum Cu [51][52][53]. Most psychiatric disorders, especially SZ and BD are related to an inflammatory reaction by the activation of the glia in the neural tissue [54,55]. On the other hand, obesity/overweight is associated with increased inflammation in SZ and BD patients [56,57].…”
Section: Discussionmentioning
confidence: 99%